Are you better? A multi‐centre study of patient‐defined recovery from Complex Regional Pain Syndrome. (1st December 2017) - Llewellyn, A.; McCabe, C.S.; Hibberd, Y.; White, P.; Davies, L.; Marinus, J.; Perez, R.G.S.M.; Thomassen, I.; Brunner, F.; Sontheim, C.; Birklein, F.; Schlereth, T.; et al.
Abstract: Background: Complex Regional Pain Syndrome (CRPS) symptoms can significantly differ between patients, fluctuate over time, disappear or persist. This leads to problems in defining recovery and in evaluating the efficacy of therapeutic interventions. Objectives: To define recovery from the patients' perspective and better understand their priorities for treatment approaches. Methods: Establishing an international consortium, we used a 2‐Round Delphi‐based study in eight countries across Europe and North America. Participants ≥18 years who met, or had met, Budapest clinical criteria were included. Round 1 participants completed the statement: 'I would/do consider myself recovered from CRPS if/because…' alongside demographic and health questionnaires. Data were thematically organised and represented as 62 statements, from which participants identified and ranked their recovery priorities in Round 2. Results: Round 1 ( N = 347, 80% female, 91% non‐recovered) dominant ICF themes were: activities of daily living; bodily functions; external factors; participation and personal factors. The top five priority statements in Round 2 ( N = 252) were: no longer having (1) CRPS‐related pain, (2) generalised pain and discomfort, (3) restricted range of movement, (4) need for medication, (5) stiffness in the affected limb. With very few exceptions, priorities were consistent, irrespective of patient demographics/geography. Symptoms affecting daily activities were among those most frequently reported. Conclusions: Our data showed a small number of themes are of highest importance to CRPS patients' definition of recovery. Patients want their pain, movement restriction and reliance on medication to be addressed, above all other factors. These factors should therefore be foremost concerns for future treatment and rehabilitation programmes. Significance: Those with longstanding CRPS may no longer meet diagnostic criteria but still be symptomatic. Defining recovery is therefore problematic in CRPS. Our study has identified patients' definition of recovery from CRPS, in order of priority, as relief from: their CRPS‐related pain, generalised pain, movement restriction, reliance on medication, and stiffness.